Monitoring and early warning model. Case of the district of Pueblo Libre, 2013-2018 - Garrafa Aragón, Hernán (2019)
Insecurity caused by the growth of violence, is a social phenomenon that is affecting the way and quality of life of people. In Lima city, this is caused by multiple factors: Social, economic, political, etc., currently It is generalizing and replicating not only at provincial level also at regional and country level, especially in department capitals, this has resulted in the increase in crime in its different modalities: Homicides, injuries, theft, illicit drug traffic, kidnapping, family violence, which can be cataloged in urban violence and organized violence. This research presents a monitoring and early warning model based on four phases: a) Information talked through a survey, b) determination of factors associated with the perception of insecurity, using correlations and decision tree c) determination of unsafe areas, based on the factors associated with the perception of insecurity, using insecurity indicators, d) mapping of unsafe areas; with the purpose of supporting the effective management of citizen security.